2015
DOI: 10.1063/1.4937438
|View full text |Cite
|
Sign up to set email alerts
|

Very large strain gauges based on single layer MoSe2 and WSe2 for sensing applications

Abstract: Here, we propose a strain gauge based on single-layer MoSe2 and WSe2 and show that, in these materials, the strain induced modulation of inter-valley phonon scattering leads to large mobility changes, which in turn result in highly sensitive strain gauges. By employing density-functional theory bandstructure calculations, comprehensive scattering models, and the linearized Boltzmann equation, we explain the physical mechanisms for the high sensitivity to strain of the resistivity in single-layer MoSe2 and WSe2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 27 publications
0
37
0
Order By: Relevance
“…Therefore, the optical and electrical properties of 1Ls may be strongly influenced by the exciton-and carrierphonon scattering between valleys at room and elevated temperatures 19,[21][22][23] . It has been proposed that tensile strain can alter the energy separation between those two states associated with the direct and indirect gaps, affecting the scattering rates [24][25][26][27] . Consequently, we expect that the altered energy separation under strain may lead to observable fingerprints in the optical spectra of the material.…”
Section: Strain As a Probementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the optical and electrical properties of 1Ls may be strongly influenced by the exciton-and carrierphonon scattering between valleys at room and elevated temperatures 19,[21][22][23] . It has been proposed that tensile strain can alter the energy separation between those two states associated with the direct and indirect gaps, affecting the scattering rates [24][25][26][27] . Consequently, we expect that the altered energy separation under strain may lead to observable fingerprints in the optical spectra of the material.…”
Section: Strain As a Probementioning
confidence: 99%
“…We propose that origin of the strong strain dependence of γ KK−KQ arises from the near degeneracy of the KK and KQ excitons, so that slight shifts in the relative positions of the valleys can have a dramatic impact on scattering rates. In fact, the energy separation between the KQ and KK states, E KQ−KK , is expected to increase due to weaker (stronger) coupling between the orbitals contributing to the K (Q) point of CB under tensile strain [24][25][26][27]39 . Such a shift in the relative energies of the states can lead to a rapid decrease in the scattering rate due to a reduction in the density of available final states in the scattering process 24 .…”
Section: A Effect Of Strain On Linewidthsmentioning
confidence: 99%
“…For such a comparison in the case of back-gated Schottky barrier transistors with 2D channels, a 2D material which exhibits a prominent Schottky barrier current branch as well as a thermal branch observable above the measurement noise floor, needs to be chosen. WSe2, which is an important member of the family of two-dimensional transition metal dichalcogenides (TMDs) 18,24,[40][41][42][43][44][45] is known to satisfy these requirements 18, 46 . In order to fabricate back-gated WSe2 SB-FETs, flakes of WSe2 were micro-mechanically exfoliated on top of substrates with 90nm SiO2 thermally grown on highly doped silicon. Flakes of various thicknesses were identified by means of optical contrast after proper calibration and atomic force microscopy (AFM) in tapping mode.…”
Section: Necessity Of a New Modelmentioning
confidence: 99%
“…However, as it was demonstrated later using time-dependent electromechanical measurements, the increased apparent piezoresistive coefficients were actually due to charge trapping and detrapping on the surface of depleted Si, whereas the intrinsic piezoresistvity of the nanostructured material is essentially the same as that of bulk (Milne et al, 2010). Recent studies on semiconducting metal oxide thin films and nanostructures, e.g., on TiO 2 (Fraga et al, 2012), MoO 3 (Wen et al, 2014), and ZnO (Kaps et al, 2017); as well as on layered transition metal dichalcogenides, e.g., MoS 2 (Nayak et al, 2014;Manzeli et al, 2015), MoSe 2 , WSe 2 (Hosseini et al, 2015), and PtSe 2 (Li et al, 2016;Wagner et al, 2018) showed highly strain dependent electronic properties, giving rise to quite high GFs comparable to those of Si and Ge (e.g. 441 for MoO 3 nanobelts, −148 for MoS 2 monolayers or −85 for PtSe 2 thin films).…”
Section: Introductionmentioning
confidence: 99%